'An Earthquake Shocked Up the Land!' Children's Communication During Play With Siblings and Friends. Issue 1 (1st July 2014) - Leach, Jamie; Howe, Nina; Dehart, Ganie
Abstract The construction of shared meanings strategies (e.g., introductions, extensions) and use of internal state language (e.g., references to mental states) during play were examined across two relationship contexts (siblings and friends) in 65 focal kindergarten‐aged children (M age = 56.4 months; SD = 5.71 months). Strategies to construct shared meanings were associated with play session; specifically focal children employed introductions more often with their siblings whereas positive/neutral responses and prosocial strategies were used more frequently with their friends. Findings regarding birth order position indicated that older focal children were more likely to engage in non‐maintenance (e.g., negative) behaviors and explanations with their siblings whereas younger focal children employed extensions of play ideas more often with their siblings than friends. Associations between shared meaning strategies and internal state language were positively correlated across both relationship contexts, with more significant associations found in the sibling play session. Findings highlight the high level of sophisticated play interaction among children during play; these interactions were rich and varied and are discussed in light of recent research and theory.